Chaihu-Longgu-Muli decoction improves sleep disorders by restoring orexin-A function in CKD mice - Cao, Xin-li; Peng, Xue-mei; Li, Gong-bo; Ding, Wei-sen; Wang, Kai-zhen; Wang, Xiao-lei; Xiong, Yan-ying; Xiong, Wei-jian; Li, Fan; Song, Min (Frontiers in Endocrinology, 2023)
Introduction Chaihu-Longgu-Muli decoction (CLMD) is a well-used ancient formula originally recorded in the “Treatise on Febrile Diseases” written by the founding theorist of Traditional Chinese Medicine, Doctor Zhang Zhongjing. While it has been used extensively as a therapeutic treatment for neuropsychiatric disorders, such as insomnia, anxiety and dementia, its mechanisms remain unclear. Methods In order to analyze the therapeutic mechanism of CLMD in chronic renal failure and insomnia, An adenine diet-induced chronic kidney disease (CKD) model was established in mice, Furthermore, we analyzed the impact of CLMD on sleep behavior and cognitive function in CKD mice, as well as the production of insomnia related regulatory proteins and inflammatory factors. Results CLMD significantly improved circadian rhythm and sleep disturbance in CKD mice. The insomnia related regulatory proteins, Orexin, Orexin R1, and Orexin R2 in the hypothalamus of CKD mice decreased significantly, while Orexin and its receptors increased remarkably after CLMD intervention. Following administration of CLMD, reduced neuron loss and improved learning as well as memory ability were observed in CKD mice. And CLMD intervention effectively improved the chronic inflflammatory state of CKD mice. Discussion Our results showed that CLMD could improve sleep and cognitive levels in CKD mice. The mechanism may be related to the up-regulation of Orexin-A and increased phosphorylation level of CaMKK2/AMPK, which further inhibits NF-κB downstream signaling pathways, thereby improving the disordered inflammatory state in the central and peripheral system. However, More research is required to confirm the clinical significance of the study.